Insulin degludec - Vishakha V Jain; Omprakash Gupta (Wolters Kluwer Medknow Publications, 2013)
Insulin analogues have revolutionized the treatment of diabetes mellitus, and the advent of newer insulin analogues have provided better glycemic control with lesser incidence of hypoglycemia. Insulin degludec is a second-generation, ultra-long-acting acylated basal insulin analogue that possesses a flat, stable glucose-lowering effect in patients with type 1 or type 2 diabetes mellitus. Findings from clinical trials have demonstrated that new-generation, once-daily basal insulin degludec provides similar A1C control as compared to insulin glargine, both administered as basal-oral therapy or in combination with insulin aspart, with the added benefits of lower rates of hypoglycemia, particularly nocturnal hypoglycemia.